Continuous erector spinae plane block for pain management in laparoscopic liver resection case report. Issue 3 (July 2020) - Piangatelli, Cristiano; Dalla Bona, Enrico; Tavoletti, Diego; Rosanò, Elisabetta; Mocchegiani, Federico; Vivarelli, Marco; Cerutti, Elisabetta
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Pain after liver resection can be difficult to manage. Epidural anesthesia (EA) is an effective technique in pain control in this surgery. However, postoperative coagulopathy and hypotension due to autonomic nervous system block in high-risk patients, may result that the EA is an inadequate analgesic technique in according to enhanced recovery after surgery (ERAS) recommendations for liver surgery. Regional block techniques have been recommended for liver surgery in ERAS guidelines. Erector spinae plane (ESP) block is a recent block described for thoracic and abdominal surgeries and provides both somatic and visceral analgesia. We describe a high-risk patient with cardiac dysfunction and Parkinson's disease who underwent laparoscopic right liver resection for hepatocellular carcinoma. Satisfactory intra and postoperative analgesia was achieved by a combined continuous ESP block, transversus abdominis plane (TAP), and oblique subcostal TAP blocks. Surgery and postoperative period was uneventful. No opioids were administered during hospitalization. A combined of thoracic and abdominal wall blocks can be an effective approach for intra and postoperative analgesia in high-risk patients undergoing laparoscopic liver resection. Further clinical research is recommended to establish the effectiveness of the ESP block as an analgesic technique in this surgery. Abstract : Résumén: El dolor posterior a una resección hepática puede ser difícil de manejar. La anestesia epidural (AE) es una técnica efectiva para el control del dolor en esta cirugía. Sin embargo, la coagulopatía y la hipotensión postoperatorias debido al bloqueo del sistema nervioso autónomo en pacientes de alto riesgo, puede hacer que la AE sea una técnica analgésica inadecuada, de acuerdo con las recomendaciones de la recuperación mejorada después de cirugía (ERAS, por las iniciales en inglés de Enhanced Recovery After Surgery) para cirugía hepática. Se han recomendado las técnicas de bloqueo regional para cirugía hepática en las guías ERAS. El bloqueo del plano erector de la espina (BEE) (ESP, por las iniciales en inglés de erector spinae plan block ) es una técnica reciente, para cirugías torácicas y abdominales, que brinda analgesia tanto somática como visceral. Se describe aquí un paciente de alto riesgo con disfunción cardiaca y enfermedad de Parkinson que se sometió a resección laparoscópica del lóbulo derecho del hígado por carcinoma hepatocelular. Se logró analgesia intra y postoperatoria eficaz mediante una combinación de bloqueo continuo ESP, y bloqueos del plano transverso abdominal (PTA) y del plano transverso abdominal subcostal oblicuo. La cirugía y el periodo postoperatorio transcurrieron sin novedad y no se administraron opioides durante la hospitalización. La combinación de bloqueos combinados torácicos y de la pared abdominal pueden ser un abordaje efectivo para la analgesia intra y postoperatoria en pacientes de alto riesgo que se someten a resección hepática laparoscópica. Se recomienda continuar con la investigación clínica a fin de establecer la efectividad del bloqueo ESP como técnica anestésica para esta cirugía.